2011
DOI: 10.1186/1471-2202-12-17
|View full text |Cite
|
Sign up to set email alerts
|

Identification of alternatively spliced Dab1 and Fyn isoforms in pig

Abstract: BackgroundDisabled-1 (Dab1) is an adaptor protein that is essential for the intracellular transduction of Reelin signaling, which regulates the migration and differentiation of postmitotic neurons during brain development in vertebrates. Dab1 function depends on its tyrosine phosphorylation by Src family kinases, especially Fyn.ResultsWe have isolated alternatively spliced forms of porcine Dab1 from brain (sDab1) and liver (sDab1-Li) and Fyn from brain (sFyn-B) and spleen (sFyn-T). Radiation hybrid mapping loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…We did not detect either Dab1 217 or Dab1 271 in our study; however, it should be noted that both of these isoforms introduce in-frame premature termination codons (PTC), which may promote RNA degradation through nonsense-mediated mRNA decay (NMD) (5). Dab1 variant 5 contains exons 9b/c (3,20,46), whose homologues have also been detected in chicken, lizard, and pig (3,29,31). Unlike the inclusion of exons 9b/9c in mouse variant 5, 9b/9c inclusion in chicken and pig is accompanied by concurrent exclusion of exons 7 and 8, producing an isoform homologous to the variant 6 identified in the present study.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…We did not detect either Dab1 217 or Dab1 271 in our study; however, it should be noted that both of these isoforms introduce in-frame premature termination codons (PTC), which may promote RNA degradation through nonsense-mediated mRNA decay (NMD) (5). Dab1 variant 5 contains exons 9b/c (3,20,46), whose homologues have also been detected in chicken, lizard, and pig (3,29,31). Unlike the inclusion of exons 9b/9c in mouse variant 5, 9b/9c inclusion in chicken and pig is accompanied by concurrent exclusion of exons 7 and 8, producing an isoform homologous to the variant 6 identified in the present study.…”
Section: Discussionsupporting
confidence: 52%
“…The genomic organization of Dab1 is unusually complex and highly conserved in different species (3,10,31 (3,20,46). All three Dab1 isoforms retain the intact PI/PTB domain at the N terminus but differ in the middle tyrosine-enriched region or in the C terminus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, splicing of exons 9b/9c and exons 7/8 is often mutually exclusive [69,76], suggesting coordinated regulation of the exclusion and inclusion of these exons during development. It would be of interest to investigate whether Nova also promotes exons 7/8 inclusion along with exons 9b/9c exclusion, and whether isoforms that exclude exons 7/8 are increased in Nova2 −/− mice along with isoforms that include exons 9b/9c.…”
Section: Additional Splicing Events Regulate Dab1 Activity and Neuronmentioning
confidence: 99%
“…Nevertheless, scattered pieces of information also show that Fyn may play a role in adipogenesis in addition to regulating energy expenditure. A recent study performed in pig indicates that a substantial level of Fyn mRNA can be detected in WAT (14). Using a comparative functional genomics approach, it has also been reported that the adipose Fyn expression is increased in obese rats (15).…”
mentioning
confidence: 98%